2019
DOI: 10.1101/2019.12.16.877449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opponent processes in visual memories: a model of attraction and repulsion in navigating insects’ mushroom bodies

Abstract: 19Solitary foraging insects display stunning navigational behaviours in visually complex natural 20 environments. Current literature assumes that these insects are mostly driven by attractive 21 visual memories, which are learnt when the insect's gaze is precisely oriented toward the goal 22 direction, typically along its familiar route or towards its nest. That way, an insect could return 23 105 106This principle can be directly applied to recapitulate idiosyncratic routes, given a set of visual 107 memori… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Importantly, this study shows that ants uses familiar terrestrial cues while navigating backward. In addition to the attractive memories facing toward the nest, the hypothesis that homing ants use a collection of repulsive visual memories facing away from the nest and possibly stored during their outbound trip was put forward (Le Möel & Wystrach, 2019). In the light of this hypothesis, visual navigation forward or backward can then simply be achieved by using the relative familiarity between both sets of opposite valence memories.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, this study shows that ants uses familiar terrestrial cues while navigating backward. In addition to the attractive memories facing toward the nest, the hypothesis that homing ants use a collection of repulsive visual memories facing away from the nest and possibly stored during their outbound trip was put forward (Le Möel & Wystrach, 2019). In the light of this hypothesis, visual navigation forward or backward can then simply be achieved by using the relative familiarity between both sets of opposite valence memories.…”
Section: Resultsmentioning
confidence: 99%
“…How can ants recognise views backward? This is a puzzling question given that the assumption of current models of visual homing states that views must be retinotopically aligned to provide directional information (Ardin, Peng, Mangan, Lagogiannis, & Webb, 2016;Baddeley et al, 2012;Collett, Graham, & Collett, 2017;Le Möel & Wystrach, 2019;Möller, 2012;Murray et al, 2020;Narendra et al, 2013;Wystrach, Mangan, Philippides, & Graham, 2013;Zeil, Hofmann, & Chahl, 2003) although some other processes may be also at work . Recently, it has been suggested that ants may perform some sort of mental rotation to compare misaligned views (Ardin, Mangan, Wystrach, & Webb, 2015;, which may be achieved if views are encoded in the frequency domain (Stone et al, 2017).…”
Section: Mental Rotation or Combining Attractive And Repulsive Views?mentioning
confidence: 99%
See 1 more Smart Citation